2018
DOI: 10.1534/genetics.118.301249
|View full text |Cite
|
Sign up to set email alerts
|

Gene Birth Contributes to Structural Disorder Encoded by Overlapping Genes

Abstract: The same nucleotide sequence can encode two protein products in different reading frames. Overlapping gene regions encode higher levels of intrinsic structural disorder (ISD) than nonoverlapping genes (39% 25% in our viral dataset). This might be because of the intrinsic properties of the genetic code, because one member per pair was recently born in a process that favors high ISD, or because high ISD relieves increased evolutionary constraint imposed by dual-coding. Here, we quantify the relative contribution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…Young genes ( Willis and Masel, 2018 ; Wilson et al, 2017 ; Foy et al, 2019 ; Mukherjee et al, 2015 ) and domains ( Bornberg-Bauer and Albà, 2013 ; Buljan and Bateman, 2009 ; Ekman and Elofsson, 2010 ; Moore and Bornberg-Bauer, 2012 ) have been reported to have high ISD, although some have claimed this depends on taxon ( Vakirlis et al, 2018 ). We use IUPred to estimate ISD from amino acid sequence alone, allowing estimation across large-scale genomic data sets that contain many sequences of undetermined structure ( Mészáros et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Young genes ( Willis and Masel, 2018 ; Wilson et al, 2017 ; Foy et al, 2019 ; Mukherjee et al, 2015 ) and domains ( Bornberg-Bauer and Albà, 2013 ; Buljan and Bateman, 2009 ; Ekman and Elofsson, 2010 ; Moore and Bornberg-Bauer, 2012 ) have been reported to have high ISD, although some have claimed this depends on taxon ( Vakirlis et al, 2018 ). We use IUPred to estimate ISD from amino acid sequence alone, allowing estimation across large-scale genomic data sets that contain many sequences of undetermined structure ( Mészáros et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In support of this, an analysis of ISD in mice found that young genes have higher ISD than old genes, while random non-genic sequences tend to show the lowest levels of ISD [98]. Although the observed trend may have partly resulted from a subset of young genes derived by overprinting [74], higher ISD in young genes was also seen among overlapping gene pairs [127]. Whether this trend holds over shorter timescales is debated [77, 128].…”
Section: Models and Mechanisms Of De Novo Gene Birthmentioning
confidence: 99%
“…Another approach to infer the genealogy of overlapping genes is the codon-usage method. It is based on the assumption that the ancestral gene, which has co-evolved over a long period of time with the other viral genes, has a distribution of synonymous codons significantly closer to that of the viral genome than the de novo gene (Keese and Gibbs, 1992;Sabath et al, 2012;Pavesi et al, 2013;Willis and Masel, 2018). Due to the shortness of most overlapping genes, the method has been improved, with the aim to evaluate the correlation between the codon-usage patterns of overlapping and non-overlapping genes with a Fig.…”
Section: In Overlapping Genes Under Asymmetric Evolution the Most Varmentioning
confidence: 99%